THE RELATIONSHIP BETWEEN PARENT-CHILD INTERACTION AND CHILDREN AT RISK OF EXPERIENCING SPEECH DELAY IN CHILDREN AGED 18 MONTHS - 3 YEARS IN WANASARI RESIDENTIAL AREA, 2022 - Vingka Anba Luthfi Milazizah; Hilda Meriyandah Agil; Riris Ocktryna (Rena Cipta Mandiri, 2023)
Background: The interaction of the mother with the child becomes an important part of the child's development. By interacting can be established an approach, giving attention to affection, instilling the ethical teachings of manners, improving his ability to learn something, as well as knowing everything that happens to him. The form of interaction between mother and child can be in the form of eating together, playing, accompanying studies, reading storybooks or fairy tales before going to bed. Speech delay can be seen from the fact that if parents not only speak to their child but also use a wide variety of words, the child's speech skills will develop quickly. Speech delay is a child who has speech delay usually due to watching too often so that it does not stimulate the child to speak and only makes the child to listen instead of speaking, but in its treatment can be done speech therapy involving gross motor and balance. Research Objectives: To determine the relationship between parents and children with speech delay in children aged 18 months – 3 years in Wanasari Housing in 2022 Research method: This research method uses a cross- sectional design. The sampling technique is Non probability sampling, with a total of 72 respondents. The analysis in this study used a fisher exact test with a meaningfulness level of α = 0.05. Results: Based on data analysis used using the fisher exact test P Value 0.03 < 0.05. Conclusion: There is a relationship between parents and children's interaction with the risk of speech delay in children aged 18 months – 3 years at Kartika Wanasari Housing in 2022.